Independent predictors of in-stent restenosis after drug-eluting stent implantation for ostial right coronary artery lesions. (1st August 2017) - Watanabe, Yusuke; Takagi, Kensuke; Naganuma, Toru; Kawamoto, Hiroyoshi; Fujino, Yusuke; Ishiguro, Hisaaki; Tahara, Satoko; Kurita, Naoyuki; Hosawa, Koji; Nakamura, Shotaro; Nakamura, Sunao
Abstract: Objectives: We evaluated the angiographic patterns and predictors of in-stent restenosis (ISR) for ostial lesions of the right coronary artery (RCA) to clarify the mechanism of insoluble restenosis. Background: Although ISR of the RCA still occurs, limited data is available regarding the associated angiographic findings. Methods: Between January 2005 and September 2013, we recruited consecutive patients undergoing routine angiography 6–18 months after implantation of a drug-eluting stent (DES). Multiple logistic regression analysis was used to determine the independent predictors of ISR, and the adjusted odds ratios (aOR) and 95% confidence intervals (95% CI) were calculated. Results: Routine angiography revealed that 45 of 131 patients (34.3%) had RCA-ISR, which were classifiable by occlusion type into ostial (24 cases), proximal (17 cases), diffuse (3 cases), and total (1 case). By multivariable analysis, early generation DES was the only independent predictor of overall ISR (aOR, 3.54; 95% CI, 1.59–7.87; p  = 0.002). In a subgroup analysis of each focal ISR pattern, early generation DES (aOR, 7.76; 95% CI, 2.15–28.0; p  = 0.002) was associated with increased risk of ostial ISR. On the contrary, larger stent (aOR, 0.21; 95% CI, 0.05–0.84; p  = 0.027) was associated with decreased risk of ostial ISR. Furthermore, a ratio of the stent to post-balloon size > 1.10 (aOR, 3.93; 95% CI, 1.30–11.8; p  = 0.002) and good left ventricular contractility (ejection fraction > 60%) (aOR, 8.27; 95% CI, 1.76–39.0; p  = 0.008) were associated with increased risk of proximal ISR when stent fracture was observed. Conclusion: The focal pattern of RCA-ISR was mostly observed after DES implantation, and the mechanisms of proximal and ostial ISR differed.